Doctors' attitudes to health centres - Silverstone, Rosalie (1980)
In one Inner London health district many doctors seemed reluctant to work in health centres. To investigate the reasons, 44 general practitioners in two matched groups were interviewed. Those working in health centres appreciated the advantages of pleasant premises and the presence of a primary health care team. Other doctors believed health centres were disliked by patients, were bureaucratic in organization, and involved difficult interpersonal relationships. These were confirmed as real problems by health centre doctors. Thus, reluctance to join health centre practices is based on a realistic appraisal of the drawbacks. Recommendations are made.